ANALISIS PENGGUNAAN BUKU CERITA BERGAMBAR DALAM MENDORONG LITERASI DIGITAL DENGAN MEDIA CHROMEBOOK PADA PESERTA DIDIK KELAS IV SDN BUGANGAN 01 - Dewi, Kuntari Candra; Nuvitalia, Duwi; Azizah, Annisa Nur; Agustini, Ferina (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The aim of this research is to determine the digital literacy level of fourth grade students at SD N Bugangan 01 East Semarang. Researchers used descriptive research with qualitative methods to achieve the objectives of this research. This research was carried out from March to April 2024, class IV of SD N Bugangan 01 East Semarang was the place where this research was conducted. Data collection methods include observation, documentation, and interviews with Mrs. Annisa Nur Azizah, class IV teacher. A total of 23 class IV students provided the required learning data. The research results show that students fulfill all aspects of digital literacy indicators, namely the application of digital literacy (reading) in learning, the use of digital media platforms in learning, the use of digital devices and the search for digital-based learning resources. Based on the results and discussions presented by the researchers, the efforts made by the school to encourage digital literacy for class IV students by using picture story books were successfully implemented and obtained good results, where students were enthusiastic in implementing digital literacy.